Fresh water aquaculture fish consumption in Malaysia and heavy metals risk exposure to consumers - Abu Bakar, Ibrahim; Ayob, Mohd Khan; Abdullah Sani, Norrakiah (2013)
Background: Fresh water aquacultures fish are exposed to many chemical contaminations include heavy metal residues. It is important to know the level of heavy metal risk exposure based on the fish consumption. Objectives: The objectives of this study were to determine the amount of the fish consumption [specifically red tilapia (Oreachromis sp), keli (Clarias spp.) and patin (Pangasius sutchii)]. in Malaysia, the quantity of heavy metal residues (namely arsenic, cadmium, mercury and plumbum) in the fish and the level of the risk exposure.